2022
DOI: 10.3389/fphys.2022.938555
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Receptor PxylOR11 Mediates Repellency of Plutella xylostella to Aromatic Volatiles

Abstract: Insects can use plant volatiles to guide certain behaviors, such as courtship, mating, host positioning, and habitat selection. Plutella xylostella is a global agricultural pest and has always been closely studied, but relatively few studies assess the molecular mechanism of P. xylostella exposed to plant volatiles. In this study, we analyzed the role of the odorant receptor PxylOR11 when P. xylostella is exposed to plant volatiles. Our analysis of tissue expression demonstrated that PxylOR11 is expressed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…OR11 of Plutella xylostella could also detect benzyl alcohol and clustered with BmorOR64 (Liu et al. , 2022), but the OR tree revealed that BmorOR64 clustered into the PintOR8 clade rather than the PintOR26 clade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OR11 of Plutella xylostella could also detect benzyl alcohol and clustered with BmorOR64 (Liu et al. , 2022), but the OR tree revealed that BmorOR64 clustered into the PintOR8 clade rather than the PintOR26 clade.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds with benzene rings should be further studied in the future. Interestingly, a study of mammalian ORs activated by acetophenone found that they shared some conserved amino acid residues but did not cluster in the same subfamilies in the OR phylogenetic tree (Liu et al, 2022), suggesting that in addition to constructing a homologous gene tree, key conserved sites of acetophenone activated ORs can be predicted in insects. To date, although some insect odorant receptors of acetophenone have been identified, such as OR28 of Anopheles gambiae (Del Mármol et al, 2021), OR15 of A. aegypti (Zeng et al, 2019), and OR25 of Spodoptera littoralis (Caballero et al, 2021), further research is needed to investigate conserved sites.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Plant volatile organic compounds (PVOCs) act as semiochemicals constituting the key factor in implementing this strategy. Benzyl alcohol, a vital semiochemical in agricultural pest control, exerts a regulatory effect on the behavior of insects, acting as a repellent, 9 attractant 10 or antifeedant. 11 The potential impact of benzyl alcohol on the chemical communication system of aphids remains largely unexplored, and it is worth investigating.…”
Section: Introductionmentioning
confidence: 99%